(untitled) (Journal of Bangladesh Academy of Sciences, 2016)
The activity concentrations of radionuclides and their respective annual effective dose rates produced by 226Ra, 232Th and 40K were measured by using high purity germanium (HPGe) detector of relative efficiency 20%. The activity concentrations of 226Ra, 232Th and 40K in the sand samples were found to vary from 22.83 ± 4.11 to 100.21 ± 2.39 BqKg-1, 68.76 ± 2.86 BqKg-1 to 297.37 ± 4.32 BqKg-1 and 75.87 ± 15.75 to 161.81 ± 19.90 BqKg-1 with mean values 48.76, 126.11 and 292.38 Bqkg-1, respectively. For sediment samples the corresponding radionuclides ranged between 12.11 ± 1.99 and 31.64 ± 1.64 BqKg-1, 18.94 ± 1.90 BqKg-1 and 71.11 ± 2.88 BqKg-1 and 182.73 ± 19.81 BqKg-1 and 345.77 ± 21.07 BqKg-1, with mean values 19.67, 32.13 and 243.38 Bqkg-1, respectively. The absorbed dose rate was estimated to the range from 30.50 to 242.93 nGyh-1 with an average value of 74.87 nGyh-1. The estimated outdoor annual effective dose varied between 0.22 and 1.79 mSv/year with a mean value of 0.55 mSv/year, which is higher than the world average for outdoor annual effective dose (0.07 mSv/year). The external hazard indices for the samples varied from 0.17 to 1.43 with the average value of 0.44, which is less than the unity. The average value of radium equivalent activity was estimated and found to be 161.40 BqKg-1 which is less than the acceptable limit of world average value of 370 BqKg-1. Journal of Bangladesh Academy of Sciences, Vol. 40, No. 1, 45-55, 2016